ASYMPTOMATIC HYPERURICEMIA AS A POTENTIAL METABOLIC RISK FACTOR FOR CORONARY ARTERY CALCIFICATION IN PATIENTS WITH ATRIAL FIBRILLATION OR HEART FAILURE - Milena Pasheva; Yoto Yotov; Miglena Nikolova; Daniela Gerova; Atanas Angelov; Bistra Galunska (Peytchinski Publishing, 2021)
Purpose: To assess the role of asymptomatic hyperuricemia for the presence and severity of coronary arterial calcium (CAC) in adults with different cardiovascular (CV) pathology and its association with conventional CV risk factors. Material/Methods: Adults (n=81) of both genders were divided into controls: with moderate- to high risk without known CVD; AF-group: CVD-patients with paroxysmal or persistent atrial fibrillation in sinus rhythm, HF-group: heart failure subjects with preserved ejection fraction. A structured interview was performed at admittance for evaluation of the classical CVD risk factors. CAC score (CACS) was determined by multislice computed tomography. Routine laboratory parameters, including uric acid (UA), were extracted from medical documentation. Descriptive statistics, Mann-Whitney U-test, one-way ANOVA, chi-square test, Spearman's correlation, and multiple linear regression analysis were applied. The predictive power of serum UA was evaluated using receiver operating characteristic (ROC) analysis. Statistical significance was considered at p<0.05. Results: Serum UA was significantly higher in subjects with CACS=1-99AU (p=0.030), and with CACS≥100AU (p=0.067) vs. patients without CACS. Within the UA tertiles, highest CACS was found in the tertile with highest serum UA. UA revealed positive relation with CACS (r=0.35, p=0.002), age (r=0.25, p=0.027), body mass index (0.27, p=0.017), waist circumference (r=0.44, p<0.0001), triglycerides (r=0.29, p=0.001), and creatinine (r=0.54, p<0.0001). Multiple linear regression analysis revealed significant association between UA as dependent variable and waist circumference (β=0.63, p=0.061), serum triglycerides (β=0.37, p=0.028), creatinine levels (β=0.45, p<0.0001). Conclusions: Asymptomatic hyperuricaemia could be an important metabolic factor negatively affecting the chronic cardio-vascular pathology besides the conventional risk factors.